China's policy in the Arctic: tradition and modernity - Valery N. Konyshev; Mariia A. Kobzeva (Сравнительная политика, 2016)
Abstract: The article describes the features of China's policy in the Arctic region, taking into account their relationship with the political and cultural traditions, which have a long history. Ambiguities in the assessments of intentions and prospects of China's policy in the Arctic is largely due underestimation of ties by the Western experts. The authors believe that the current China's foreign policy in general and toward the Arctic, in particular, is formed under the infl uence of such factors as the combination of «soft» and «hard» methods of management, existing sharp contradictions between the elites in the political leadership of the state, and the tradition of long-term planning in strategy. In accordance with this, the Arctic dimension of modern China foreign policy, seeks to achieve the strategic goal of access to the resources of the region in many directions simultaneously. The most important instruments include the revision of the legal status of the Arctic, an active part in the work of international organizations and active bilateral inter-state cooperation, avoiding open confrontation, “waiting” policy and incremental measures aimed at the gradual squeezing of competitors.